Enhanced accuracy in gravity-based intravenous infusion using pulse oximeter drop counting and measured single-drop weights - Daeseok Oh; Myoung Jin Ko; Jae Hwan Kim; Yeiheum Park; Sungho Moon (Anesthesia and Pain Medicine, 2025)
Background Intravenous (IV) fluid therapy is essential and widely used; however, it is associated with high error rates, largely due to human factors, necessitating constant and careful monitoring by medical staff. Gravity-based systems are prone to errors, whereas electronic pumps, though more accurate, are limited by size, cost, and complexity. In this study, the impact of single-drop weight measurement and real-time light source monitoring on the accuracy of gravity-based infusion systems was evaluated. Methods Gravity-based IV sets with IV infusion flow regulators (IIFRs) from three manufacturers were tested using 1,000 ml of 0.9% saline. The drops per min and the drop weight were recorded using a pulse oximeter (PO), which served as a light source. The flow rates from the PO group were compared with those from the manufacturer’s drop volume (C) and the IIFR groups. The mean absolute percentage error (MAPE) of predicted versus actual volumes was analyzed along with correlations between the residual volume and drop rate. Results The PO group values were statistically closer to those of the actual measurements than the C and IIFR groups values (P < 0.05), demonstrating higher accuracy and lower MAPE, except at 300 ml/h when than those of the C group, independent of residual volume. The residual volume strongly correlated with the drop rate (r > 0.9). Conclusions Real-time drop measurements using light sources combined with single-drop weight assessment improve the accuracy of these systems. Integrating POs into IV sets may enhance clinical precision and reduce provider workload.